Peningkatan Kemampuan Literasi Matematika Mahasiswa Melalui Penerapan Model RME Pada Perkuliahan Konsep Dasar Geometri dan Pengukuran - Karjiyati, Victoria; Supriatna, Irfan; Agusdianita, Neza; Yuliantini, Nani (UNIB Press, 2022)
Education in Indonesia is currently promoting literacy education. One of the highlights is mathematical literacy. Mathematical literacy ability in Indonesia is still relatively low. This is evidenced by the results of the 2018 Program for International Assessment (PISA) survey, in the field of mathematics, Indonesia is ranked 72 out of 78 countries with a score of 379. The objectives of the research are: to improve students' mathematical literacy skills in the Basic Concepts of geometry and measurement lectures in PGSD FKIP Study Program, Bengkulu University by applying a realistic mathematics education (RME) model. This research uses action research method (Action Research). Data collection techniques aspects of the management of the learning process will collect data in the form of information through observation, and tests of mathematical literacy skills then summarized and described in the form of a data matrix. Data were analyzed through qualitative descriptive. The results of the study have been carried out in lectures by applying the RME model in the Basic Concepts of Geometry and Measurement course. Students' mathematical literacy test results also increased. The highest increase in the aspect of context literacy.